Aplikasi Theory Of Planned Behavior Terhadap Niat Beli Produk Skincare Halal Pada Gen Z - Nudia Febriani Putri; Kristina Anindita Hayuningtias (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The halal industry has a strategic role in improving the economy. Halal certificates are an important factor in skincare products. The aim of the research is to analyze the influence of attitudes, subjective norms and behavioral control on halal skincare products on Gen Z. The population in this study is generation Z in Semarang City and the sample taken was 205 respondents. The sampling technique used was a purposive sampling technique. The analysis technique in the research uses multiple linear regression analysis with the help of SPSS version 26. The results of this research show that attitude has no effect on the intention to buy halal skincare products. Meanwhile, norms and behavioral control have a positive and significant effect on the intention to purchase halal skincare products. Keywords: attitude; subjectivtive norms; behavior control;purchase intention